Gender aspects of social entrepreneurship in Russia - A. L. Andrushhenko; E. L. Kruglova (Цифровая социология)
This research paper analyses gender aspects of social entrepreneurship in the Russian Federation (hereinafter referred to as RF, Russia). In the context of growing social problems and their actualisation, the development of this activity becomes important for both society and the state. The topic of gender relations in the Russian environment is debatable as certain professions in society are associated with certain gender characteristics, including the field of entrepreneurship. The results of many studies show that it is often seen as a masculine phenomenon, and entrepreneurs being aggressive, bold, calculating, and risk-taking. However, social entrepreneurship is associated with more “feminine” characteristics, such as ethics of care, compassion, and altruism. Within the framework of this research paper, the authors will analyse the gender characteristics of the studied phenomenon and identify the role of businesswomen in the process of its formation and development on the Russian territory. The analysis of the gender aspects of social entrepreneurship in Russia will identify the obstacles and challenges faced by businesswomen. The role of the state and public organisations while supporting gender entrepreneurship and creating equal opportunities for men and women in the field will also be considered. Thus, the purposes of this article are to raise awareness and understanding of the gender aspects in social entrepreneurship and to contribute to the creation of a more inclusive and equitable business environment in the RF.